Nuevos tratamientos psicológicos en tabaquismo: las intervenciones a distancia - Fletes, Isabel; Sánchez, Beatriz; Quesada, Mónica; Carreras, José María; Maldonado, Belén; Sánchez, Leopoldo (Psicooncología, 2006)
Smoking prevalence is still elevated in our country. Nevertheless most of smokers do not have an easy acces to smoking cessation treatments. Development of non face-to-face programs though quitlines and internet has been possible thanks to new technologies advance. The objective of this paper is to review the research about new non face-to-face smoking cessation treatments and to analyse its clinic feasibility in a public hosptial with previous experience in actual treatments.